Determinants of public health expenditures in Pakistan - Faisal Abbas; Ulrich Hiemenz (University of Bonn, Center for Development Research (ZEF), 2011)
This study describes the macroeconomic determinants of health care spending in a broad context using time series data from Pakistan on economic, demographic, social, and political variables. The data spans a period from 1972- 2006 and was analyzed using cointegration and error correction approaches. All variables were found to be first difference stationary and the results confirm the presence of one cointegrating vector. This proves the existence of a long-run relationship between public health care expenditures and the other variables used in the model. The income elasticity of public health care expenditures is estimated at 0.23. As this value is less than unity it suggests that, contrary to most of the Organization for Economic Co-operation and Development (OECD) countries health care qualifies as a necessity in Pakistan. Urbanization and unemployment are variables that have a negative effect on health care expenditures, with elasticity values of -1.29 and -0.32 respectively, implying that it is costly to provide health care to residents of remote rural areas of Pakistan.
Keywords: 330; Public Health Expenditures; Unemployment; Urbanization; Cointegration; time series; Pakistan; Gesundheitskosten; Arbeitslosigkeit; Urbanisierung; Kointegration; Schätzung; Pakistan